CLASSIFICATION OF ART TERMS IN UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2024)
The article explores the intricate landscape of art terminology, focusing on the differences and similarities between Uzbek and English languages. It is categorized various art terms, highlighting cultural nuances and the impact of language on artistic expression. The classification is based on various artistic disciplines, including visual arts, performing arts and literary arts, providing a comprehensive framework for understanding how these terms function within both languages. Through a comparative analysis, the article reveals the challenges of translating art concepts between Uzbek and English, often shaped by differing cultural contexts, historical backgrounds and aesthetic values. Thus, it is emphasized the importance of recognizing these distinctions to foster better communication and appreciation of art across linguistic boundaries. The research findings are underscored by practical examples, illustrating the dynamic interplay between language and culture.